Effect of Low Degradable Sunflower Meal and Seed on Growth, Some Carcass and Blood Measurements in Awassi Lambs - Shehab, Safwan Luqman; Mohammed, Omar Dheyaa; Ahmed, Falah Hassan (Journal of agricultural, environmental and veterinary sciences, 2021)
The study was conducted to investigate the effect of lowering protein degradability in sunflower meal or protein and fat in sunflower seeds on performance and carcass parameters. Sixteen Awassi lam. sixteen Awassi lambs were used with an average weight (28.37 ± 0.80 kg) , aged 3.5-4 months , lambs were divided into four groups, the first group fed on a diet sunflower cake contained 11% of its components, the second group fed on a diet similar to the first group, except that the sunflower cake was low degradable, the third group was fed on a diet contained 11% sunflower seed as a substitute for sunflower cake, while the fourth group fed a diet containing 11% low degradable Sunflower seed. The results indicated that feeding the low degradable sunflower cake in the second group led to a significant increase (p
Keywords: sunflower meal and seed; degradability; performance